Responder
The two numbers are \( \frac{30+6\sqrt{17}}{5} \) and \( \frac{30-6\sqrt{17}}{5} \).
Solución
To solve this problem, we can set up a system of equations based on the given information. Let's denote the two numbers as \( x \) and \( y \).
From the first piece of information, we have:
\[ x + y = 12 \]
From the second piece of information, we have:
\[ x^2 + y^2 = \frac{21}{2}xy \]
We can solve this system of equations to find the values of \( x \) and \( y \).
Let's solve the system of equations.
Solve the system of equations by following steps:
- step0: Solve using the substitution method:
\(\left\{ \begin{array}{l}x+y=12\\x^{2}+y^{2}=\frac{21}{2}xy\end{array}\right.\)
- step1: Solve the equation:
\(\left\{ \begin{array}{l}x=12-y\\x^{2}+y^{2}=\frac{21}{2}xy\end{array}\right.\)
- step2: Substitute the value of \(x:\)
\(\left(12-y\right)^{2}+y^{2}=\frac{21}{2}\left(12-y\right)y\)
- step3: Simplify:
\(144-24y+2y^{2}=\frac{21}{2}y\left(12-y\right)\)
- step4: Move the expression to the left side:
\(144-24y+2y^{2}-\frac{21}{2}y\left(12-y\right)=0\)
- step5: Calculate:
\(144-150y+\frac{25}{2}y^{2}=0\)
- step6: Rewrite in standard form:
\(\frac{25}{2}y^{2}-150y+144=0\)
- step7: Multiply both sides:
\(2\left(\frac{25}{2}y^{2}-150y+144\right)=2\times 0\)
- step8: Calculate:
\(25y^{2}-300y+288=0\)
- step9: Solve using the quadratic formula:
\(y=\frac{300\pm \sqrt{\left(-300\right)^{2}-4\times 25\times 288}}{2\times 25}\)
- step10: Simplify the expression:
\(y=\frac{300\pm \sqrt{\left(-300\right)^{2}-4\times 25\times 288}}{50}\)
- step11: Simplify the expression:
\(y=\frac{300\pm \sqrt{300^{2}-28800}}{50}\)
- step12: Simplify the expression:
\(y=\frac{300\pm 60\sqrt{17}}{50}\)
- step13: Separate into possible cases:
\(\begin{align}&y=\frac{300+60\sqrt{17}}{50}\\&y=\frac{300-60\sqrt{17}}{50}\end{align}\)
- step14: Simplify the expression:
\(\begin{align}&y=\frac{30+6\sqrt{17}}{5}\\&y=\frac{300-60\sqrt{17}}{50}\end{align}\)
- step15: Simplify the expression:
\(\begin{align}&y=\frac{30+6\sqrt{17}}{5}\\&y=\frac{30-6\sqrt{17}}{5}\end{align}\)
- step16: Evaluate the logic:
\(y=\frac{30+6\sqrt{17}}{5}\cup y=\frac{30-6\sqrt{17}}{5}\)
- step17: Rearrange the terms:
\(\left\{ \begin{array}{l}x=12-y\\y=\frac{30+6\sqrt{17}}{5}\end{array}\right.\cup \left\{ \begin{array}{l}x=12-y\\y=\frac{30-6\sqrt{17}}{5}\end{array}\right.\)
- step18: Calculate:
\(\left\{ \begin{array}{l}x=\frac{30-6\sqrt{17}}{5}\\y=\frac{30+6\sqrt{17}}{5}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{30+6\sqrt{17}}{5}\\y=\frac{30-6\sqrt{17}}{5}\end{array}\right.\)
- step19: Calculate:
\(\left\{ \begin{array}{l}x=\frac{30+6\sqrt{17}}{5}\\y=\frac{30-6\sqrt{17}}{5}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{30-6\sqrt{17}}{5}\\y=\frac{30+6\sqrt{17}}{5}\end{array}\right.\)
- step20: Check the solution:
\(\left\{ \begin{array}{l}x=\frac{30+6\sqrt{17}}{5}\\y=\frac{30-6\sqrt{17}}{5}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{30-6\sqrt{17}}{5}\\y=\frac{30+6\sqrt{17}}{5}\end{array}\right.\)
- step21: Rewrite:
\(\left(x,y\right) = \left(\frac{30+6\sqrt{17}}{5},\frac{30-6\sqrt{17}}{5}\right)\cup \left(x,y\right) = \left(\frac{30-6\sqrt{17}}{5},\frac{30+6\sqrt{17}}{5}\right)\)
The solution to the system of equations is:
\[ (x, y) = \left(\frac{30+6\sqrt{17}}{5}, \frac{30-6\sqrt{17}}{5}\right) \text{ or } (x, y) = \left(\frac{30-6\sqrt{17}}{5}, \frac{30+6\sqrt{17}}{5}\right) \]
Therefore, the two numbers are \( \frac{30+6\sqrt{17}}{5} \) and \( \frac{30-6\sqrt{17}}{5} \), or \( \frac{30-6\sqrt{17}}{5} \) and \( \frac{30+6\sqrt{17}}{5} \).
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución